Ketentuan Usia Pernikahan di Afrika Utara (Mesir, Tunisia, Maroko, Aljazair, Libya) - Nur Fadhilah Novianti (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
The North African region consists of countries where the majority of the population is Muslim, so family law provisions are regulated based on Islamic law by adopting or combining the views of certain schools of thought. One of the issues that is developing in the study of family law is the age of marriage. This research aims to explore the dynamics of the development of marriage age regulations in Muslim countries. This type of research is qualitative, with a normative approach, where the primary data source used, namely Family Law Laws in each country, is collected through library research or literature study, and analyzed descriptively qualitatively. The research results show that in several countries, the marriage age provisions vary; Egypt (18 years), Tunisia (18 years), Morocco (18 years), Algeria (19 years), and Libya (20 years). The majority of countries allow marriage dispensations and the marriage age requirement is above the child's age requirement. The implications of this research will be useful for academics who wish to study further contemporary issues of international family law as a scientific reference.